Blueberry (Vaccinium ashei Reade) cv. Brightwell in vitro establishment with silver thiosulfate - Antonio Ayub, Ricardo; de Azevedo Pasqualini, Ana Paula; Neves dos Santos, Jesse; Vasconcelos Botelho, Renato (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2017)
During in vitro culture the ethylene accumulation inside the culture recipient can be detrimental to culture. An alternative to avoid the formation of ethylene that has brought good results in seedling development is the addition of silver thiosulfate (STS), an inhibitor of ethylene perception. Based on this knowledge, the present study aimed to evaluate the influence STS o n the in vitro establishment of blueberry (Vaccinium ashei Reade) cv. Brightwell. Nodal segments were used, in WPM culture medium, supplemented with 5 mg L-1 2iP and STS at concentrations of 0, 15, 30, 45 e 60 µM. After 60 days it was assessed: the percentage of surviving explants and that developed leaf primordia, number of buds with shoots, length of longer budding and number of leaves. The obtained data were submitted to analysis of variance and, when significant, compared by Duncan test (p ≤ 0.05) and shown by polynomial regression. The effect of STS concentration used wassignificant at 5% probability for the parameters number of buds with shoots and leaves and favored by the use of 45µM STS.